2013
DOI: 10.1038/srep03104
|View full text |Cite
|
Sign up to set email alerts
|

Novel dielectric anomalies due to spin-chains above and below Néel temperature in Ca3Co2O6

Abstract: We bring out novel dielectric behavior of a spin-chain compound, Ca 3 Co 2 O 6 , undergoing Néel order at (T N 5) 24 K. It is found that the virgin curve in the plot of isothermal dielectric constant (e') versus magnetic-field lies outside the 'butterfly-shaped' envelope curve well below T N (e.g., 2.6 K), with a signature of a partial arrest of the high-field magnetoelectric (ME) phase in zero-field after travelling through magnetic-field-induced magnetic transitions. This behavior is in contrast to that obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 59 publications
5
44
0
Order By: Relevance
“…The observed frequency dependence may reflect slow electric-dipole dynamics, which are yet to be unraveled. The frequency dependencies in both ac susceptibility and complex dielectric properties are scarce for stoichiometric (that is, undoped) compounds, barring a few exceptions [27,28]. The demonstrations of distinct memory effect both in magnetic and dielectric studies support multiglass behavior of FTO as was first time observed in the ME multiglass SrTi 0.98 Mn 0.02 O 3 [6].…”
Section: Resultsmentioning
confidence: 69%
“…The observed frequency dependence may reflect slow electric-dipole dynamics, which are yet to be unraveled. The frequency dependencies in both ac susceptibility and complex dielectric properties are scarce for stoichiometric (that is, undoped) compounds, barring a few exceptions [27,28]. The demonstrations of distinct memory effect both in magnetic and dielectric studies support multiglass behavior of FTO as was first time observed in the ME multiglass SrTi 0.98 Mn 0.02 O 3 [6].…”
Section: Resultsmentioning
confidence: 69%
“…This kind of unusual ME behaviour due to complex dynamics of spins and dipoles is rare in the literature; for example, a magnetodielectric phase-coexistence is observed in the spin-chain compound Ca 3 Co 2 O 6 without any fingerprints of such a phase-co-existence in isothermal magnetization measurements, despite strong intrinsic magnetodielectric coupling in this complex compound. 27 The results suggest that spin-induced ferroelectricity in RCrTiO 5 may be governed by DM interactions due to the Cr moments, significantly influenced by R-moments. It has to be noted that a finite magnetodielectric coupling (dielectric constant as a function of H, which consists higher order coupling term as well) for GdCrTiO 5 exists even for temperatures up to 20 K. 15 This fact could arise from magnetic exchange frustration resulting from competing exchange interactions between Gd and Cr moments, active even above magnetic ordering (> 10 K).…”
Section: 26mentioning
confidence: 88%
“…In the case of Dy member, it was noted that, in addition to the multiferroic behavior setting in at (T N =) 58 K, there is an additional transition at temperatures (T) well below T N , as though there is a 'reentrant phenomenon' into a complex multiglass-like state below 10 K. Such a phenomenon is not so commonly known particularly among undoped stoichiometric compounds in the field of multiferroics, barring a few examples (see, Ref. 5,7 and articles cited therein), though the concept of multi-glass was originally discussed in some doped materials [8]. It is therefore of interest to study low temperature properties of other members of this family well below their respective T N .…”
mentioning
confidence: 99%